2010
DOI: 10.1038/ja.2010.149
|View full text |Cite
|
Sign up to set email alerts
|

The genus Actinoallomurus and some of its metabolites

Abstract: In the search for novel antibiotics, natural products continue to represent a valid source of bioactive molecules. During a program aimed at identifying previously unreported taxa of actinomycetes as potential source of novel compounds, we isolated hundreds of different representatives of a new group, initially designated as 'Alpha' and independently described as Actinoallomurus. We report on a PCR-specific method for the detection of this taxon, on appropriate growth conditions and on a pilot-screening progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 29 publications
0
50
0
Order By: Relevance
“…Although antimicrobial activity of the isolates from plant roots was generally worse than that of soil-dwelling organisms, 50% of Sphaerisporangium strains, which were not isolates from rhizospheric soil performed bioactivity, additionally, the genera Microbispora, Actinoallomurus, Verrucosispora and others also produced antibiotics. Pozzi et al 32 concluded that Actinoallomurus strains produce antibiotic compounds at high frequency, and Tiwari et al 33 reported that rare actinomycetes possess the capacity to produce many useful metabolites and represent one of the most important sources of new bioactive compounds. We are very interested in endophytic actinomycete strains which is difficult to isolate from the soil.…”
Section: Potential Of Secondary Metabolites Produced By Endophytic Acmentioning
confidence: 99%
“…Although antimicrobial activity of the isolates from plant roots was generally worse than that of soil-dwelling organisms, 50% of Sphaerisporangium strains, which were not isolates from rhizospheric soil performed bioactivity, additionally, the genera Microbispora, Actinoallomurus, Verrucosispora and others also produced antibiotics. Pozzi et al 32 concluded that Actinoallomurus strains produce antibiotic compounds at high frequency, and Tiwari et al 33 reported that rare actinomycetes possess the capacity to produce many useful metabolites and represent one of the most important sources of new bioactive compounds. We are very interested in endophytic actinomycete strains which is difficult to isolate from the soil.…”
Section: Potential Of Secondary Metabolites Produced By Endophytic Acmentioning
confidence: 99%
“…DSMZ 13491, prepared by inoculating a frozen cell stock into 30 ml of AFT medium (2% glucose, 0.2% yeast extract, 0.8% soybean meal, 0.5% tryptone, 0.1% NaCl, 0.4% CaCO 3 , adjusted to pH 7.2 with 0.1 N NaOH before sterilization) and incubating for 72-96 h, was transferred into 200 ml of fresh AFT medium. The production of antibacterial activity was monitored over time by depositing 10 ml of a microbial extract, prepared as described by Pozzi et al, 3 onto Muller Hinton Agar (Difco Laboratories, Detroit, MI, USA) plates, previously inoculated with 10 5 cfu ml À1 Staphylococcus aureus ATCC 6538P or Micrococcus luteus ATCC 10240. An inhibition halo was clearly observed on M. luteus plates after 24 h of cultivation, whereas only a weak activity was visible on the S. aureus plates.…”
mentioning
confidence: 99%
“…Pozzi et al 5 reported that Actinoallomurus strains possess the ability to produce various bioactive compounds. Many Actinoallomurus strains have been found among our isolates.…”
Section: Introductionmentioning
confidence: 99%